(untitled) (Al-Qamar, 2024)
Due to Pakistan’s diverse cultural and political landscape, essential democratic pillars like freedom of speech and expression remain challenging. This study investigates the status of free expression in Pakistan by qualitatively analyzing scholarly literature, legal papers, news stories, and interviews. In this study, we have discussed the fundamental right pertaining to free speech which is guaranteed in the Constitution of Islamic Republic of Pakistan, 1973. We also have Examined that how religious beliefs and political unrest are sociocultural elements affecting self-censorship. Online censorship regulations and surveillance provide additional issues in the digital world, which are explored in the paper. Critics of the have endured threats, harassment, and job losses, according to primary evidence gathered from interviews with journalists and legal experts. Although the Constitution of Pakistan promises the right to free expression, the results show that open debate and dissent have been severely limited over the years due to practical restrictions, and even more limits have just come into effect.